Woolly Monkey–HBV Infection in Squirrel Monkeys as a Surrogate Nonhuman Primate Model of HBV Infection. Issue 3 (3rd January 2020) - Chen, Christopher Y.; Winer, Benjamin Y.; Chavez, Deborah; Guerra, Bernadette; Brasky, Kathleen M.; Eng, Stacey; Salas, Eduardo; Tam, Danny; Simmons, Joe H.; Abee, Christian R.; Delaney, William E.; Ploss, Alexander; et al.
Abstract : Development of curative therapies for chronic hepatitis B virus (HBV) infection will likely require new animal models. Here, we evaluate HBV infection in squirrel monkeys based on the high‐sequence homology of the HBV receptor, Na+/taurocholate co‐transporting peptide (NTCP), between humans and squirrel monkeys. HBV PreS1 peptide was examined for binding human and squirrel monkey NTCP. Immunodeficient Fah −/−, NOD, Rag1 −/−, Il2Rg null (FNRG) mice engrafted with human or squirrel monkey hepatocytes were challenged with HBV or Woolly Monkey HBV (WMHBV). In addition, adult squirrel monkeys were inoculated with HBV, WMHBV, adeno‐associated virus containing an infectious genome of HBV (AAV‐HBV), and AAV‐WMHBV. Finally, neonate squirrel monkeys were assessed for the potential of chronic infection with WMHBV. PreS1 peptide efficiently bound to human and squirrel monkey NTCP but not to mouse or capuchin NTCP. FNRG mice engrafted with squirrel monkey hepatocytes were susceptible to infection by WMHBV but not human HBV. Similarly, adult squirrel monkeys could be infected with WMHBV but not human HBV, whereas chimeric mice engrafted with human hepatocytes were susceptible to HBV but not WMHBV. Infection of squirrel monkeys with AAV‐WMHBV yielded maximum viremia of 10 8 genomes/mL with detectable virus for up to 8 months. Notably, covalently closed circular DNA was detected in the liver of these animals. Infection of neonates with WMHBV led to detectable viremia for up to 6 months. Conclusions : Adult and neonate squirrel monkeys exhibited prolonged WMHBV viremia lasting 6‐8 months. This is greater than twice the duration of viremia achieved in other nonhuman primates and suggests that squirrel monkeys may be a suitable model for testing HBV therapeutics. Abstract :